The Effect of Differentiated Learning Models in Physical Education on Enhancing Students’ Learning Interest at Hang Tuah 1 Senior High School, Surabaya - Danilson Danilson; Luqmanul Hakim (Journal of Comprehensive Science, 2026)
The problem examined in this study is whether differentiated learning models have an effect on increasing learning interest among students at SMA Hang Tuah 1 Surabaya. This study aims to understand the effect of differentiated learning models on improving students’ learning interest in physical education at the senior high school level, as well as to measure the extent of the increase in learning interest through the application of differentiated learning models and questionnaire distribution. This research was conducted at SMA Hang Tuah 1 Surabaya using a quantitative approach with a quasi-experimental method and a non-randomized group pretest–posttest design. The study involved Phase F11.6 students totaling 30 participants, divided into an experimental group of 15 students who received differentiated learning treatment and a control group of 15 students who received no treatment, selected through simple random sampling. The results showed a significant effect in the experimental group, with the posttest mean score higher than the pretest (25.07 > 22.67). Hypothesis testing also indicated a significant increase in learning interest (p = 0.004 < 0.05). It can be concluded that differentiated learning models effectively improve students’ interest in physical education learning.